2017
DOI: 10.3233/bsi-170167
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric green fluorescent protein as a protein standard for small angle scattering

Abstract: Abstract. Protein small angle scattering (SAS) has become increasing important in structural biochemistry, due to the increased performance and specification of new instruments and advances in the software and hardware used to analyse the data. Whilst all of this is encouraging, there is a lack of standardised experimental methodology within the community. Although a number of protein standards are currently used in SAS experiments to allow accurate molecular weight determination, each has specific advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Previous work on eGFP revealed that the protein exists in dimers. 46 When no YCl 3 is present, SAXS data indicates the presence of cylinders with a diameter of 30 Å and lengths of ∼80 Å, consistent with dimers as illustrated in the inset in Fig. 2a (Table SI, ESI † and Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Previous work on eGFP revealed that the protein exists in dimers. 46 When no YCl 3 is present, SAXS data indicates the presence of cylinders with a diameter of 30 Å and lengths of ∼80 Å, consistent with dimers as illustrated in the inset in Fig. 2a (Table SI, ESI † and Fig.…”
Section: Resultssupporting
confidence: 57%
“…In order to determine these interactions we first fitted our SAXS data with a cylindrical form factor 46 to obtain information on the dimerisation and aggregation of small numbers of proteins. The results obtained are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with previous work on eGFP, where it was found that the protein exists in dimers. 103…”
Section: Characterization 1 Saxs Analysismentioning
confidence: 99%
“…These results are in agreement with previous work on eGFP, where it was found that the protein exists in dimers. 100 Electrophoretic Mobility Measurement. We performed electrophoretic mobility µ e measurements on 1 mL protein solutions of 2 mg/mL at 20 • C in a NaCl 10 mM solution using a Zetasizer Nano ZS (Malvern, UK) at a detector angle of 13 • and a 4 mW 633 nm laser beam to determine the charge of eGFP following Roosen-Runge, et al 91 Care was taken in order to have the same pH with the buffer used in phase diagram determination.…”
Section: Saxs Analysismentioning
confidence: 99%